2022
DOI: 10.1007/s00415-022-11249-x
|View full text |Cite
|
Sign up to set email alerts
|

Abuse and revictimization in adulthood in multiple sclerosis: a cross-sectional study during pregnancy

Abstract: Background Knowledge concerning exposure to abuse in adulthood and in pregnancy in people with multiple sclerosis (MS) is sparse. Objective To determine the occurrence of adult abuse and abuse in relation to pregnancy in women with MS and their risk of revictimization (repeated abuse as adults after childhood abuse). Methods This cross-sectional study comprised pregnant women from the Norwegian Mother, Father and Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
0
0
0
Order By: Relevance
“…The largest case-control study combined physical and verbal abuse into one abuse exposure but did not include sexual abuse [29]. These two studies did not find associations between childhood abuse and MS. Interestingly, emotional and sexual abuse were the most common abuse categories associated with MS in the studies that reported associations [31,36,38].…”
Section: Aces and Ms Risk: Summary Of Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…The largest case-control study combined physical and verbal abuse into one abuse exposure but did not include sexual abuse [29]. These two studies did not find associations between childhood abuse and MS. Interestingly, emotional and sexual abuse were the most common abuse categories associated with MS in the studies that reported associations [31,36,38].…”
Section: Aces and Ms Risk: Summary Of Evidencementioning
confidence: 99%
“…Furthermore, exposure to abuse and neglect in childhood increases the risk of experiencing abuse as an adult [79]. A Norwegian cohort study found a two-fold higher risk of experiencing repeated abuse as an adult after experiencing childhood abuse among women with MS compared to women without MS [38]. People with MS and a history of ACEs can therefore be exposed to a vicious chain of repeated stressful events and unfavorable coping.…”
Section: Childhood Adversity: Moderating Factorsmentioning
confidence: 99%